Extracellular Matrix Enzymes and Immune Cell Biology - McMahon, Meagan; Ye, Siying; Pedrina, Jess; Dlugolenski, Daniel; Stambas, John (Frontiers in Molecular Biosciences, 2021)
Remodelling of the extracellular matrix (ECM) by ECM metalloproteinases is increasingly being associated with regulation of immune cell function. ECM metalloproteinases, including Matrix Metalloproteinases (MMPs), A Disintegrin and Metalloproteinases (ADAMs) and ADAMs with Thombospondin-1 motifs (ADAMTS) play a vital role in pathogen defence and have been shown to influence migration of immune cells. This review provides novel insights into the role of ECM enzymes in immune cell migration and function and discusses opportunities and limitations for development of diagnostic and therapeutic strategies targeting metalloproteinase expression and activity.